Dot and the Kangaroo: Chapter 5 - Ethel C. Pedley
Dot and the Kangaroo, written in 1899, is a children's book by Ethel C. Pedley about a little girl named Dot who gets lost in the Australian outback and is eventually befriended by a kangaroo and several other marsupials. The book was adapted into a stage production in 1924 and a film in 1977.[1]